Analysing Comovements between Dirty and Green Energies: An Econometric Approach - João, Esperança; Dias, Rui; Galvão, Rosa; Alexandre, Paulo; Teixeira, Nuno; Gonçalves, Sidalina (Journal of Ecohumanism, 2025)
This study analyses the movement patterns between clean energy indices and oil benchmarks such as Brent and WTI from 7 January 2022 to 8 November 2024, intending to verify whether clean energy indices can serve as effective risk diversification instruments. The research focuses on the Nasdaq Clean Edge Green Energy (CELS), S&P Global Clean Energy (SPGTCLEN), Clean Energy Fuels (CLNE) indices and the Invesco Wilderhill Clean Energy (PBW) ETF. The results show that Brent influences the prices of the CELS, CLNE and PBW indices but is unaffected by SPGTCLEN or WTI. WTI has a broad influence, influencing all the other indices. CELS only affects WTI and CLNE, while SPGTCLEN influences CELS and CLNE without influencing the oil markets. CLNE affects CELS, SPGTCLEN and PBW but not Brent or WTI. PBW influences WTI and CLNE but does not affect the other markets. WTI is a key indicator that affects all the other indices, while Brent is the most independent. This indicates that investors can reduce their exposure to oil risk by investing in clean energy indices such as CELS and CLNE, which have limited influences on each other. In conclusion, this study has contributed to understanding the dynamics of movement between clean energy indices and oil benchmarks over the period analysed, offering relevant implications for risk management and portfolio diversification.